Pinkas, kahal, and the mediene : the records of Dutch Ashkenazi communities in the eighteenth century as historical sources - Litt, Stefan, 1969- (Studies in Jewish history and culture, 2008)
Scholars of the rich history of the Jews in the Dutch Republic have tended to concentrate on the remarkable story of Amsterdam. This study examines the records of four provincial Ashkenazi communities in eighteenth-century Netherlands including The Hague, Middelburg, Leeuwarden, and Oisterwijk.